ANALISA TEMPORAL SEBARAN SUHU PERMUKAAN LAUT TAHUN 2018 HINGGA 2020 DENGAN DATA CITRA TERRA MODIS - Aulia Azizah; Hendrata Wibisana (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2020)
ABSTRACTSea surface temperature (SPL) information is the most important water quality parameter in the ocean, especially in coastal areas. Remote sensing technology with Terra Modis satellite data is used for periodic monitoring of SPL changes. The purpose of this study was to analyze the temporal distribution of SPL on the coast of Malang, East Java. The data used are SPL data from Terra-MODIS satellite sensors in May 2018, 2019 and 2020. Analysis of the data used is descriptive analysis which includes temporal analysis of SPL based on SPL fluctuations in graphical form. The results showed that the temporal variation of the 2018-2020 SPL on the coast of Malang tends to increase. The SPL value in 2018 varies between 25 ° C - 26 ° C while in 2019 it varies between 26 ° C - 27 ° C and in 2020 it ranges between 30 ° C - 31 ° C. The highest average SPL value from 2018 - 2020 is in 2020 with a temperature of 30.58 ° C. In an effort to model sea surface temperatures used calculations using mathematical models. From the results obtained it can be concluded that the most optimal mathematical model is derived from the wavelength of 667 nm on May 23, 2020 with the equation model y = -0,498ln (x) + 27,936 which results in a correlation value of R = 0.6561.Keywords: sea surface temperature, terra modis, satellite, mathematical models.ABSTRAKInformasi suhu permukaan laut (SPL) merupakan parameter kualitas perairan yang paling penting di lautan terutama kawasan pesisir. Teknologi penginderaan jauh dengan data satelit Terra-MODIS digunakan untuk pemantauan perubahan SPL secara berkala. Tujuan penelitian ini adalah menganalisis sebaran temporal SPL di pesisir pantai Malang, Jawa Timur. Data yang digunakan adalah data SPL dari sensor satelit Terra Modis bulan Mei 2018, 2019 dan 2020. Analisis data yang digunakan adalah analisis deskriptif yang meliputi analisis SPL secara temporal berdasarkan fluktuasi SPL dalam bentuk grafik. Hasil penelitian menunjukan bahwa variasi temporal SPL tahun 2018-2020 di pesisir Malang cenderung mengalami peningkatan. Nilai SPL tahun 2018 bervariasi antara 25°C – 26°C sedangkan tahun 2019 bervariasi antara 26°C – 27°C dan tahun 2020 berkisar antara 30°C – 31°C. Nilai SPL rata-rata tertinggi dari tahun 2018 – 2020 berada pada tahun 2020 dengan suhu 30,58°C. Dalam upaya memodelkan suhu permukaan laut digunakan perhitungan dengan menggunakan model matematika. Dari hasil yang diperoleh dapat disimpulkan bahwa model matematis yang paling optimal berasal dari panjang gelombang 667 nm pada tanggal 23 Mei 2020 dengan model persamaan y = -0,498ln(x) + 27,936 yang menghasilkan nilai korelasi R = 0,6561.Kata Kunci: suhu permukaan laut, terra modis, satelit, model matematis.